Role of Advertisement for Brand Section in Fast Moving Consumer Goods Industry towards Consumer Buying Behavior: Investigating the Impact of Advertisement on Consumer Buying Behavior in the Fast Moving Consumer Goods Industry (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Brand picture and advertisement assume a crucial role to boost up any business execution as brand picture is a suggested tool, which can decidedly change individuals' buying behaviors, and advertisement is acting as a main thrust for any business as it is an effective source to pass on your message and remain in customer’ mind. The motivation behind this investigation is to inspect the effect of brand picture and advertisement on consumer buying behavior in the public. The main aim of this paper is to define the impact of Advertisement on brand perception in the FMCG industry, Data was analyze by utilizing distinctive statistical systems, for example, graphic measurement, Correlation analysis, and regression analysis. Consequences of our examination are robust in light of the fact that the evidence demonstrates that advertisements significantly affect consumers' buying behavior and their decisions. The examination inferred that brand picture and advertisement have a solid positive impact and significant association with Consumer buying behavior. Individuals see the brand picture with an inspirational attitude.